2002
DOI: 10.1074/jbc.m204951200
|View full text |Cite
|
Sign up to set email alerts
|

Calpain and Mitochondria in Ischemia/Reperfusion Injury

Abstract: Studies of ischemia/reperfusion (I/R) injury and preconditioning have shown that ion homeostasis, particularly calcium homeostasis, is critical to limiting tissue damage. However, the relationship between ion homeostasis and specific cell death pathways has not been investigated in the context of I/R. Previously we reported that calpain cleaved Bid in the absence of detectable caspase activation (1). In this study, we have shown that an inhibitor of the sodium/hydrogen exchanger prevented calpain activation af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
158
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(174 citation statements)
references
References 44 publications
13
158
1
2
Order By: Relevance
“…Whereas caspase-3 has been linked to degradation of small myofilament proteins (62), we did not find a role for caspase-3 in doxorubicin-induced titin degradation. Consistent with our results, Chen et al (63) reported a reduction in CK release and a decrease in infarct size following calpain but not caspase inhibition in the ischemic reperfused heart, although no clear distinction was made between necrotic and apoptotic cell death.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Whereas caspase-3 has been linked to degradation of small myofilament proteins (62), we did not find a role for caspase-3 in doxorubicin-induced titin degradation. Consistent with our results, Chen et al (63) reported a reduction in CK release and a decrease in infarct size following calpain but not caspase inhibition in the ischemic reperfused heart, although no clear distinction was made between necrotic and apoptotic cell death.…”
Section: Discussionsupporting
confidence: 82%
“…At the end of the experimental protocol, myocytes were harvested and sonicated in calcium-free assay buffer containing 63 10 mmol/liter 2-mercaptoethanol, pH 7.3) in a 96-well fluorescent plate. Samples were incubated at 37°C for 10 min, and N-succinyl-Leu-LeuVal-Tyr-7-amido-4-methylcoumarin was added to the samples for a final concentration of 50 mol/liter.…”
Section: Methodsmentioning
confidence: 99%
“…This channel has been suggested to preserve calcium homeostasis and would therefore limit calpain activation [16]. Indeed, calpain inhibition was protective in models of ischemia/reperfusion which suggests that pore opening, if it occurs, is downstream of calpain activation [17]. The study of Yue Li et al implies that similar mechanisms apply during AF.…”
mentioning
confidence: 73%
“…Bordone and Campbell, 2002;Rutledge and Whiteheart, 2002;Chen et al, 2002, among many others). The new selective and cell-permeable inhibitor described here may help to confirm or question results obtained with less specific inhibitors and to discriminate between the effects of calpain and other cellular proteases (Yamashima, 2000).…”
Section: Discussionmentioning
confidence: 99%